A reconfigurable ethernet switch for self-optimizing communication systems - Griese, Björn (2006)
Self-optimization is a promising approach to cope with the increasing complexity of today’s automation networks. The high complexity is mainly caused by a rising amount of network nodes and increasing real-time requirements. Dynamic hardware reconfiguration is a key technology for self-optimizing systems, enabling, e.g., Real-Time Communication Systems (RCOS) that adapt to varying requirements at runtime. Concerning dynamic reconfiguration of an RCOS, an important requirement is to maintain connections and to support time-constrained communication during reconfigu-ration. We have developed a dynamically reconfigurable Ethernet switch, which is the main building block of a prototypic implementation of an RCOS network node. Three methods for reconfiguring the Ethernet switch without packet loss are presented. A prototypical implementation of one method is described and analyzed in respect to performance and resource efficiency.